Sosialisasi Pentingnya Penggunaan Sistem Informasi Manajemen Rumah Sakit (SIMRS) di Rumah Sakit Umum Daerah Wakatobi, Sulawesi Tenggara: Socialization of the Importance of Using Hospital Management Information Systems (SIMRS) at Wakatobi Regional General Hospital, Southeast Sulawesi - Ode Muhammad Ady Ardyawan, La; Dewi Kusumawati, Prima; Peristiowati, Yuly (Jurnal Abdi Keperawatan dan Kedokteran, 2024)
The hospital management information system (SIMRS) is a very important and useful system for obtaining information about health, management and can be used to determine further policies. This community service aims to increase health workers understanding of the importance of SIMRS in RSUD. Wakatobi. This community service activity was carried out on 15-21 August 2024 at RSUD. Wakatobi. The community service method is carried out by means of socialization in the form of lectures and  discussions. The number of participants was 25 people to find out the officers understanding regarding SIMRS.Before being given education in the form of health socialization and answers and after delivering the material, questions and answers were conducted to re-observe participants' understanding. Evaluation of the results showed that participants understood and understood the benefits and convenience of using SIMRS in hospitals and the obstacle found in implementing SIMRS was the absence of a SIMRS team in the RSUD Organizational Structure. Wakatobi, hospital management does not encourage personnel to use SIMRS, SIMRS standard operational procedures/SPOs are not yet complete, there are no hardware and software facilities such as computers to support the implementation of SIMRS, there is no SIMRS training and special officers, the main tasks and functions (TUPOKSI) of the SIMRS organization it's not clear and the server often gets hot, the LAN often crashes. Health workers' understanding of the importance of SIMRS is increasing and health workers are motivated to use the hospital management information system after health outreach is carried out.